Current debates on the mesolithic-neolithic transition in Britain and Ireland - Thomas, Julian (Documenta Praehistorica, 2004)
In this contribution I address a series of recent publications which present revisionist accounts of the beginning of the Neolithic in the British Isles. New evidence suggests that we need to reconsider issues of population movement, diet, mobility and residence patterns. However, I conclude that a return to a model of colonisation by an agricultural population from the continent is premature, and seek to stress the distinct patterns of change that characterised Britain and Ireland respectively.
Keywords: arheološke najdbe; mezolitik; neolitik; demografski razvoj; naselja; kolonizacija; agriculture; kmetijstvo; food; prehrana; Velika Britanija; Ireland; Irska